Livedo racemosa in neurological diseases: an update on the differential diagnoses - Mitri, Fouad; Enk, Alexander; Bersano, Anna; Kraemer, Markus (European journal of neurology, 2020)
Livedo is a net-like violaceous skin pattern. It can be classified as physiological or pathological. The physiological livedo reticularis usually appears in cold conditions, whereas the pathological and irregular livedo, which persists in warm temperatures, is often labeled as ‘livedo racemosa’.
First published: 11 June 2020
Gesehen am 05.01.2022